LAND OWNERSHIP TYPE IMPACT ON INCLUSIVE URBAN REDEVELOPMENT IN SUB-SAHARAN AFRICA - E. ALABA, DARE, (IJRDO - Journal of Social Science and Humanities Research, 2017)
Tenure is the land issue of the poor; without tenure poverty reduction misses its potential to improve slum settlements and tenements. This study focused on spatial planning and security of tenure in Lokoja. Pocket of ten blighted area with very high incident of insecure tenure was identified systematic random sampling technique was employed within the clustered sampled area Regression and analysis of variance was used to test the hypothesis. Analyzed data revealed that there is a significant difference between the quality of life of squatters measured by infrastructure services and residence with secured tenure (measured by availability of title deed). The author advocates site and services provision by government, removal of bottleneck in the process of land acquisition, registration and argue for inclusion of slum dwellers in urban renewal.